Evaluating the Performance of Chinese Mutual Funds: A Study of the Application of Value-at-Risk (VaR) - Feng, Jingyan (2008)
The mutual funds in China have experienced a dramatically growth in the past three years. It has become a favourable investment tool for many small investors. However, choosing a mutual fund with excellent performance out of more than three hundred funds is a time consuming and costly process. This paper elaborates three performance measures to evaluate Chinese mutual funds and found that the traditional Sharpe Index is unable to provide accurate evaluation since the returns of mutual funds are clustered to the left graph towards to the low values and with leptokurtic distribution, suggesting violation of normality assumption. To avoid this problem, this paper applies Value-at-Risk (VaR) to replace standard deviation. However, different VaR approaches might lead to various outcomes. In order to test the precision of the newer performance measure, backtest will be conducted to assess the accuracy of Historical Simulation (HS) of VaR model, and the results of backtesting reveal that HS could provide satisfactory risk estimation to the majority sample funds. After analysing the data, this paper observed that Yin Hua, Jia Shi C, Tai Da B and Zhao Shang have the lowest VaR values. Besides, Da Cheng, Zhong Xin, Tai Da A and Tai Da B are identified as the best performance mutual funds in the sample.